2019
DOI: 10.1055/s-0039-3400259
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Palliative Care in Patients with Advanced Liver Disease

Abstract: Advanced liver disease is increasing in mortality and morbidity worldwide, as a result of growing alcohol consumption, obesity, and viral hepatitis infection. Alongside efforts to reduce these factors, it is clear that we must identify the considerable palliative care needs of these patients in order to improve quality of life and reduce symptom burden. Our review focuses on the current state of palliative and end-of-life care for patients with advanced liver disease, the significant associated symptom burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We also found that the LOS time trend per patient began to increase gradually after 2018. A possible reason for this is that, with improvement in national medical insurance policies and enhanced disease awareness among individuals, an increasing number of patients with severe liver disease (see Supplementary Figure S2A) choose to go to hospital, with a view to improving their quality of life and delaying progression of the disease through treatment (31,32). In our study, we compared medical expenditure time trends concerning patients with liver cirrhosis among various patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the LOS time trend per patient began to increase gradually after 2018. A possible reason for this is that, with improvement in national medical insurance policies and enhanced disease awareness among individuals, an increasing number of patients with severe liver disease (see Supplementary Figure S2A) choose to go to hospital, with a view to improving their quality of life and delaying progression of the disease through treatment (31,32). In our study, we compared medical expenditure time trends concerning patients with liver cirrhosis among various patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies within the past 5 years identified limited availability of PC services for patients with liver disease, leading to limited and late involvement of PC specialists, by which many potential benefits of PC may be lost. ( 10 ) In an analysis of a nationwide inpatient sample, Rush et al ( 11 ) found that only 4.5% of all ESLD‐related admissions received a PC consultation, although this increased from 1% in 2006 to 7.1% in 2012. Barnes et al ( 12 ) found that only 19% of eligible patients (defined as having ≥ 2 admissions within 6 months for decompensated cirrhosis, excluding those who were listed for liver transplantation [LT]) received “early PC” (i.e., as defined by, PC received > 30 days before death), with hospitalization costs significantly reduced in those with early PC because of a lower number of endoscopies and blood transfusions.…”
Section: Current State Of Pc For Esldmentioning
confidence: 99%
“…Early integration of palliative care (PC) for patients with ESLD and their family caregivers is recommended, ( 7 , 8 , 9 , 10 ) yet remains underutilized. ( 11 , 12 , 13 , 14 , 15 ) One of the reasons for this is a limited specialty PC workforce.…”
mentioning
confidence: 99%
“…(3)(4)(5) These factors lead to significant deterioration in patients' quality of life with immense burden on caregivers. (6) Early integration of palliative care (PC) for patients with ESLD and their family caregivers is recommended, (7)(8)(9)(10) yet remains underutilized. (11)(12)(13)(14)(15) One of the reasons for this is a limited specialty PC workforce.…”
mentioning
confidence: 99%